2014
DOI: 10.5539/ass.v11n2p103
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Green Purchase Behaviour Trend of Malaysian Consumers

Abstract: The emergence of environmental problems and the increased awareness towards green purchase behaviour have received many responses by the stakeholders' worldwide like from the government bodies, researchers, businesses, consumers and so on. Government's bodies, for example, have responded by developing and introducing their own environmentally-linked policies to be implemented in their countries, which are intended to conserve and preserve the environment. Researchers, on the other hand, are continuously conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 19 publications
1
30
1
2
Order By: Relevance
“…Rapid economic growth, coupled with increasing worldwide consumption in the last few decades, has caused environmental deterioration through over-consumption and over-utilization of natural resources (Jaiswal and Kant, 2018). Rising environmental problems such as solid wastes, ozone depletion, air pollution, global warming, and haze have emerged urgent issues for consumers, societies, business organizations, and governments (Goh and Wahid, 2014; Vazifehdoust et al., 2013). Consumers, businesses, and governments are presently faced with one of the biggest challenges of our time; that of preserving natural resources and protecting the environment (Jaiswal and Kant, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid economic growth, coupled with increasing worldwide consumption in the last few decades, has caused environmental deterioration through over-consumption and over-utilization of natural resources (Jaiswal and Kant, 2018). Rising environmental problems such as solid wastes, ozone depletion, air pollution, global warming, and haze have emerged urgent issues for consumers, societies, business organizations, and governments (Goh and Wahid, 2014; Vazifehdoust et al., 2013). Consumers, businesses, and governments are presently faced with one of the biggest challenges of our time; that of preserving natural resources and protecting the environment (Jaiswal and Kant, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A review of past literature on green purchasing and environmental management practices focused mainly on service firms in the education (Tan et al, 2017) and hospitality industries (Mahadi et al, 2017;Tang et al, 2014). Ramakrishnan et al (2015) examined green purchasing adoption among SMEs in Malaysia, whereas Goh and Abdul Wahid (2015) reviewed past studies on green purchasing behaviour of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, attitude was a pivotal factor in several papers that scrutinized the trend by Malaysian consumers to buy green products (Goh & Wahid, 2015) It is important to note that researchers have found that the factors that affected individuals' attitudes and encouraged them to buy organic food in developing countries were dissimilar to the motivations found in developed countries, and that health was the only common, crucial factor among all countries (Rana & Paul, 2017).…”
Section: Environmental Attitude In the Sustainable Consumption Contextmentioning
confidence: 99%
“…In the Tripathi's and Singh's () review of the sociopsychological antecedents of sustainable consumption, they found that environmental attitudes were a main factor among the 28 factors identified during the period from 1990 to 2014. In addition, attitude was a pivotal factor in several papers that scrutinized the trend by Malaysian consumers to buy green products (Goh & Wahid, ). Moreover, when Joshi and Rahman () reviewed 53 articles related to the attitude–behavior relationship within a green purchasing theme between 2000 and 2014, 12 studies (22.6% of the total studies) investigated the effect of attitude and only 3 of these studies indicated an insignificant relationship between attitude and with GPB.…”
Section: Environmental Attitude In the Sustainable Consumption Contextmentioning
confidence: 99%